2021
DOI: 10.1007/s10997-021-09568-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reporting quality and BoD characteristics: an empirical analysis

Abstract: The amount of literature on IR has grown over the last few years, but while particular attention has been paid to the variables that can play a role in IR adoption, IR quality and its determinants are still the subject of debate. The main determinants of IR quality outlined by the literature are firm size, industry, national context, firm performance, assurance, and to a lesser extent, corporate governance and company ownership structure. However, previous studies have usually reached conflicting results, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(106 citation statements)
references
References 173 publications
(315 reference statements)
2
58
2
4
Order By: Relevance
“…The UN 2030 Agenda as well as the most important international organizations have, therefore, managed to find an explicit solution to the issue in order to define a limit to, among others, those economic activities that -albeit profitable from a mere financial point of view -have, indeed, as a consequence, a negative impact for the environment and for the referential communities. In this, academic and scientific communities confirmed that accounting, reporting, and disclosure practices play a pivotal role in aligning the goals of the several stakeholders' strategies adopted at corporate level (Schaltegger 2020;La Torre et al 2020;Kose & Agdeniz 2021;Songini et al 2021;. In this regard, one of the COP26 outcomes was indeed related to "Transparency and Reporting", making emerge a set of rules through which countries shall be held accountable for delivering results related to their climate action plans and self-set targets under their nationally determined contributions (Kirikkaleli & Adebayo, 2020;UN Climate Change 2021a, b;Adebayo et al 2021a, b).…”
Section: Introductionmentioning
confidence: 78%
“…The UN 2030 Agenda as well as the most important international organizations have, therefore, managed to find an explicit solution to the issue in order to define a limit to, among others, those economic activities that -albeit profitable from a mere financial point of view -have, indeed, as a consequence, a negative impact for the environment and for the referential communities. In this, academic and scientific communities confirmed that accounting, reporting, and disclosure practices play a pivotal role in aligning the goals of the several stakeholders' strategies adopted at corporate level (Schaltegger 2020;La Torre et al 2020;Kose & Agdeniz 2021;Songini et al 2021;. In this regard, one of the COP26 outcomes was indeed related to "Transparency and Reporting", making emerge a set of rules through which countries shall be held accountable for delivering results related to their climate action plans and self-set targets under their nationally determined contributions (Kirikkaleli & Adebayo, 2020;UN Climate Change 2021a, b;Adebayo et al 2021a, b).…”
Section: Introductionmentioning
confidence: 78%
“…Akhtaruddin et al (2009) state that a board of directors is an important governance tool for increasing accountability and voluntary company disclosures as better monitoring, after all, will result in the public release of vast amounts of corporate data. According to the previous literature, there is no consistent results between board size and disclosure (Songini et al, 2021;Kılıç & Kuzey, 2018). Husted & de Sousa-Filho (2019) find a positive and significant effect of board size on ESG, while Orazalin (2019) and Sankara et al (2017) could not find any significant impact of board size and ESG and CSR disclosure.…”
Section: Control Variablesmentioning
confidence: 93%
“…Karamanou and Vafeas (2005) and Cheng and Courtenay (2006) also find similar results. While Songini et al (2021) find otherwise. Further, board tenure is the length of time a person serves as a director in an organization (Shiah-Hou & Cheng, 2012).…”
Section: Control Variablesmentioning
confidence: 97%
“…d. Masculinity VS Femininity -MVF: IBM studies revealed that women's values differ to a lesser degree than men in societies, while men's values differ in terms of firmness and competitiveness versus modesty and care for women's values from one society to another. e. Long-Term vs. Short-Term Orientation -LTO: This dimension was identified for the first time in a survey of students from (23) countries, in a study of their beginnings (Bond), it was found that this dimension is strongly linked to economic growth, Its values included perseverance, thrift, and relationships based on social status, in exchange for reciprocal social obligations, respect for tradition, protection of reputation, and personal fortitude and stability. f. Indulgence VC Restraint -IVR: This dimension was added in (2010) based on a study conducted by (Minkov's, 2000) that included (93) countries; It focuses on aspects not covered by the other five dimensions, as indulgence represents the free satisfaction of basic and natural human desires related to the enjoyment of life and pleasure, while self-control represents a society that controls and regulates the satisfaction of needs through strict social standards.…”
Section: Theoretical Side 21mentioning
confidence: 99%